2016
DOI: 10.1038/srep26661
|View full text |Cite
|
Sign up to set email alerts
|

Bioabsorbable zinc ion induced biphasic cellular responses in vascular smooth muscle cells

Abstract: Bioabsorbable metal zinc (Zn) is a promising new generation of implantable scaffold for cardiovascular and orthopedic applications. In cardiovascular stent applications, zinc ion (Zn2+) will be gradually released into the surrounding vascular tissues from such Zn-containing scaffolds after implantation. However, the interactions between vascular cells and Zn2+ are still largely unknown. We explored the short-term effects of extracellular Zn2+ on human smooth muscle cells (SMCs) up to 24 h, and an interesting b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
76
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 104 publications
(83 citation statements)
references
References 46 publications
6
76
0
1
Order By: Relevance
“…Compared to vascular endothelial cells, vSMCs were much less tolerable to the corroded products of zinc in vivo . In vitro , vSMCs replicated slower when cultured at 80∼120 μM zinc ion concentration . Even when Zn 2+ was low to 50 m M , the proliferative damage still occurred in a long‐term exposure experiment .…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Compared to vascular endothelial cells, vSMCs were much less tolerable to the corroded products of zinc in vivo . In vitro , vSMCs replicated slower when cultured at 80∼120 μM zinc ion concentration . Even when Zn 2+ was low to 50 m M , the proliferative damage still occurred in a long‐term exposure experiment .…”
Section: Discussionmentioning
confidence: 95%
“…Even when Zn 2+ was low to 50 m M , the proliferative damage still occurred in a long‐term exposure experiment . In addition, the free Zn 2+ also hindered the cell movement of human aortic SMCs . Therefore, the locally accumulated Zn 2+ due to the degradation of AZ31 may inhibit the vSMC expanding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, high concentrations of Zn 2+ elicited opposite effects. Gene expression profiles revealed that the most affected functional genes were related to angiogenesis, inflammation, cell adhesion, vessel tone, and platelet aggregation [26]. Since the Zn 2+ concentration is intrinsically related to the implant degradation rate, a slow corrosion rate with controlled release of Zn 2+ is desirable to maintain a low concentration profile of Zn 2+ in the local tissues, in order to benefit cellular functions [16].…”
Section: In Vitro Examinationmentioning
confidence: 99%
“…The cellular response of human bone marrow mesenchymal stem cells (hMSC) and human vascular cells (HCECs, HASMC, HAEC) to Zn 2+ was recently investigated [16,26,69,70]. According to Zhu et al [70], Zn biomaterial can support hMSC adhesion and proliferation and zinc ions can lead to enhanced regulation of genes, cell survival/growth and differentiation, extracellular matrix (ECM) mineralization, and osteogenesis.…”
Section: In Vitro Examinationmentioning
confidence: 99%